A CATHOLIC THEOLOGICAL REFLECTION ON MISSION - Frizzell, Lawrence E (Journal of Dharma, 1981)
The Catholic theology of mission was expressed in various documents of the Council, especially in the Decree on the Church’s Missionary Activity (Ad Gentes) of December 7, 1965. Critical selfexamination in the wake of the Council has alerted many Catholics to the need for inner conversion as a response to "living change." The malaise felt with regard to earlier missionary efforts may be studied in the context of Nostra Aetate and Vatican documents of recent years.